Mechanical strength of briquettes for use in blast furnaces - Lemos,Leandro Rocha (2019)
Abstract The demand for sustainable materials in the steel industry and the search for alternatives for the traditional ferriferous burdens utilized in siderurgy stimulated the development of this research. The briquetting process is a usual measure taken for recycling materials such as ironmaking waste (dust and sludge from blast furnaces), which can be reutilized in steel plants. The objective of this article is to investigate the influence of the use of organic and inorganic binders, blast furnace dust and sludge on the mechanical strength of briquettes for use in blast furnaces. The mechanical analysis was performed with the results from tumbling tests, executed to obtain the strength of each sample composition. The results exhibited adequate values of mechanical strength for samples that contained BBTL and BBTX binder, indicating that these materials acted as good binders in the briquetting process.